Learning control of robot - Lo, Kenneth Yih Hung. (2011)
The emulation of human learning has long been among the most sought after goals in the research of robotics and artificial intelligence. Human beings have the ability to learn from experience. A mechanical robot today can also learn from the past operation data to improve its performance. In this project, a learning controller based on neural network will be designed and implemented on an industrial robot. Given a desired trajectory in task space, the learning controller is able to learn and eventually drive the closed loop system to follow the trajectory as the actions are repeated.